Bionomy of Coccus pseudomagnoliarum (Kuwana) (Hemiptera: Coccidae), a new species in the fauna of Serbia - Dervišević, Marina; Stojanović, Aleksandar; Graora, Draga (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
Citricola scale, Coccus pseudomagnoliarum (Kuwana) (Hemiptera: Coccidae) was for the first time registered in Serbia in 2015 in the area of Belgrade on Celtis occidentalis L. C. pseudomagnoliarum develops one generation annually and overwinters as the second-instar nymph on host twigs. It forms numerous colonies on infested plants, and symptoms of its feeding appear in the form of drying leaves and twigs. In addition, large amounts of honeydew that this scale secretes reduce photosynthesis and transpiration in plants, which accelerates their decay. Citricola scale attracts many entomophagous insects which are able to reduce pest population. The parasitoid wasps Coccophagus lycimnia (Walker), Coccophagus piceae Erdos, Coccophagus scutellaris (Dalman), Coccophagus shillongensis (Hayat and Singh) (Aphelinidae), Cheiloneurus claviger Thomson and Metaphycus stanleyi Compere (Encyrtidae) were reared. C. piceae and M. stanleyi are new species in the fauna of Serbia. C. pseudomagnoliarum is a new host for the species M. stanleyi. The predators Coccinella septempunctata L., Exochomus quadripustulatus (L.) (Coccinellidae) and Chrysoperla carnea (Stephens) (Chrysopidae) were found in scale colonies. The most efficient natural enemy of C. pseudomagnoliarum nymphs was C. lycimnia, reducing scale populations by 11-26%.